2018
DOI: 10.1002/biot.201800137
|View full text |Cite
|
Sign up to set email alerts
|

Larger Pore Size Hollow Fiber Membranes as a Solution to the Product Retention Issue in Filtration‐Based Perfusion Bioreactors

Abstract: Tangential flow filtration (TFF) and alternating tangential flow (ATF) filtration technologies using hollow fiber membranes are commonly utilized in perfusion cell culture for the production of monoclonal antibodies; however, product retention remains a known and common problem with these systems. To address this issue, commercially available hollow fibers ranging from several hundred kilo-Daltons (kDa) to 0.65 μm in nominal pore size were tested and were all demonstrated to undergo moderate to severe product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 19 publications
5
43
1
Order By: Relevance
“…Our previous study (Pinto, Napoli, & Brower, 2020) showed an integrated continuous bioprocess with practically nonproduct retention when employing macroporous (>1 µm pore size) perfusion membranes. This observation, corroborated by Wang et al (2017) and Wang et al (2019), highlights that microfiltration membranes retain particles within its pore size range, which leads to product sieving. Whereas, submicron particles perfuse through the larger pores of macroporous hollow fiber membranes and thus overcome product sieving.…”
Section: Introductionsupporting
confidence: 70%
“…Our previous study (Pinto, Napoli, & Brower, 2020) showed an integrated continuous bioprocess with practically nonproduct retention when employing macroporous (>1 µm pore size) perfusion membranes. This observation, corroborated by Wang et al (2017) and Wang et al (2019), highlights that microfiltration membranes retain particles within its pore size range, which leads to product sieving. Whereas, submicron particles perfuse through the larger pores of macroporous hollow fiber membranes and thus overcome product sieving.…”
Section: Introductionsupporting
confidence: 70%
“…In another study, the use of ATF in place of an internal spin filter was studied, and it was found to result in higher cell densities, a higher perfusion rate, higher production (50-70%), and a longer run (Bosco et al, 2017). To overcome the product retention problem associated with TFF-and ATF-based perfusion cultures, a large pore size hollow fiber was recently used and drastically reduced product retention (Wang et al, 2019). In another study, temperature was established to be an important parameter in perfusion culture performance optimization (Wolf et al, 2019a).…”
Section: Perfusion Culture Processmentioning
confidence: 99%
“…Hence, the use of PS membranes can be equally important for related perfusion processes where expressed proteins are considered as product, but retained by PES membranes with a nominal cutoff of 0.2 μm (Karst, Serra, Villiger, Soos, & Morbidelli, 2016;Kelly et al, 2014). Alternatively, other studies identified the use of large-pore membranes of 2 μm and larger as a solution for production retention (Pinto, Napoli, & Brower, 2019;S. B. Wang, Godfrey, Radoniqi, Lin, & Coffman, 2019).…”
Section: Membrane Fouling Dynamics and Its Impact On Product Retentionmentioning
confidence: 99%